Sleep quality and its association with recovery in patients undergoing total knee arthroplasty: A systematic review: Sleep and total knee arthroplasty - Vasquez Jr., Victor M.; Ngatuvai, Micah; Sohail, Nehaa; Hansen, Joshua; Rainey, Joshua; Purcell, Richard (Journal of Surgery and Medicine, 2025)
Background/Aim: Sleep disturbances are a prevalent but often overlooked issue among patients undergoing total knee arthroplasty (TKA). These disruptions significantly contribute to increased pain, delayed functional recovery, and reduced quality of life. This systematic review examines the association between sleep quality and postoperative recovery outcomes after TKA. Methods: The review utilized five databases: PubMed, Embase, Ovid/MEDLINE, CINAHL, and Scopus. We identified studies that evaluated sleep quality and recovery outcomes in adult TKA patients. Eligible studies used validated tools such as the Pittsburgh Sleep Quality Index (PSQI), Insomnia Severity Index (ISI), and actigraphy to examine recovery metrics, including pain, mobility, and overall recovery trajectories. A narrative synthesis was conducted to identify patterns and variations across the included studies. Results: Seven studies, involving a total of 902 patients, were included in this review. Poor sleep quality is consistently correlated with adverse recovery outcomes, such as higher pain levels, slower functional recovery, and diminished quality of life. Quantitative data underscored the association between elevated PSQI scores and delayed recovery metrics. Patients with higher PSQI scores reported elevated pain levels (VAS: 3.8 vs. 1.6) and poorer functional outcomes, as indicated by significantly higher WOMAC-Physical Function scores several weeks after TKA compared to groups with less prominent insomnia (P<0.05). Conclusion: Interventions targeting sleep disturbances, such as behavioral therapies, showed promising benefits. However, methodological variability limited the generalizability of findings. This review emphasizes the critical importance of sleep quality as a modifiable factor in optimizing recovery after TKA. Integrating sleep assessments and targeted interventions, such as cognitive-behavioral therapy for insomnia (CBT-I), into perioperative care can significantly enhance recovery trajectories and patient outcomes. Future research should prioritize standardizing methodologies and investigating the effectiveness of sleep-focused strategies across diverse patient populations.